IDENTIFIKASI POTENSI AIR TANAH DI KECAMATAN MANGKUBUMI TASIKMALAYA DENGAN METODE UJI POMPA - Agung Riyadi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Pumping tests are carried out to determine how much groundwater taken from a well and what effects pumping will have on the aquifer. Theis recovery method aims to find out the aquifer characteristics such as transmisibility and permeability values. This method in principle observes the recovery of ground water surface. This reasearch location at Mangkubumi distric Tasiklamaya West Java. The value of transmisibilitas and permeabilitas in Mangkubumi district indicated the groundwater potential is good. Ground water flow (m3/day) between 684,02 at Cipawitra until 4.617,19 at Cipari Tasikmalaya. Hidrolik Conductivity between 0.39 – 2.63 (m2/day).